Selective control of ligand binding through a distal mutation that alters the protein native ensemble - Rahul Dani; Iladeiti Kurbah; Dhruv Kumar Chaurasiya; Rohan Nath; Arunkumar Krishnan; David Fushman; Athi N. Naganathan (Proceedings of the National Academy of Sciences, 2026)
Unraveling the molecular mechanisms underlying long-range mutational effects on function is a challenging prospect. In this study, we delineate the consequences of a mutation located at a site distal to the functional region in a promiscuous acyl-CoA binding domain. A W86A mutation at a distal C-terminal segment induces two-stage noncooperative unfolding in an otherwise cooperatively unfolding protein, with the mutant exhibiting properties of a molten-globule with large equilibrium fluctuations at 310 K. Under the same conditions, NMR reveals a fourfold increase of a slow-exchanging alternate conformation in the W86A mutant, relative to the wild-type. These manifest as altered dynamic and thermodynamic coupling patterns promoting significant conformational excursions of helix 1, thus stabilizing an intermediate involving unfolded or undocked helix 1. The nonnative interactions mediated by helix 1, in turn, partially occlude the ligand-binding pocket influencing function in a chain-length-dependent manner. Further, the two-stage unfolding switches to a single transition in the W86A mutant in the presence of the ligand while simultaneously suppressing the population of the alternate conformation. Our results provide insights into how mutations could trigger long-range effects through modulation of the native ensemble properties, and the uniquely interconnected nature of the underlying molecular mechanisms.